Pengaruh Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan pada PT Bussan Auto Finance (BAF) Cabang Baturaja - Dahlia Dahlia; Noviansyah Noviansyah; Leta Wahyuni (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
This study aimed to determine the influence of communication and organizational culture on employees'performance at PT. Bussan Auto Finance (BAF) Baturaja Branch.The data analysis technique used was Multiple Linear Regression. Based on the results of a partial analysis of the communication variable, it showed that there was a significant influence of communication on employees' performance at PT. Bussan Auto Finance (BAF) Baturaja Branch with a t-count value of 3,298. Based on the results of the partial analysis there was an influence of Organizational Culture on employees' performance at PT. Bussan Auto Finance (BAF) Baturaja Branch with a t value of 4.108. Simultaneously, it was found that there was a jointly significant influence between communication and organizational culture with an f-count of 54,488. The coefficient of determination (R2) obtained was 0.736. This showed that the contribution of the influence of communication and organizational culture on employees'performance was 73.6% while the remaining 26.4% was influenced by other variables outside of this study, namely work design, personality, motivation, leadership, leadership style, job satisfaction, work environment. , loyalty, commitment, and work discipline (Kasmir, 2019: 189).